Method to extract intact and pure RNA from mycobacteria - Akhtar, Shamim; Sarkar, Sampa; Mishra, Abhishek; Sarkar, Dhiman (Analytical Biochemistry, 2011)
We describe a high-yielding, simple, and aerosol-free protocol for the isolation of RNA from mycobacteria that does not require sophisticated instruments. The method yielded 50 mu g of RNA from 10(7) cells, 50 times more than a recently reported method. Our method can extract total RNA from aerobically grown bacteria and from in vitro hypoxia-induced dormant bacilli and mycobacteria residing within infected macrophages. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Dormant; Hypoxia; Mycobacteria; RNA isolation; Spheroplast; Trizol